Toward a Culture of Consequences - Stecher, Brian M. (RAND Corporation, 2010)
Performance-based accountability systems (PBASs) link incentives to measured performance to improve services to the public. Research suggests that PBASs influence provider behaviors, but little is known about PBAS effectiveness at achieving performance goals. This study examines nine PBASs that are drawn from five sectors: child care, education, health care, public health emergency preparedness, and transportation.